2009
DOI: 10.1111/j.1528-1167.2009.02161.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of androgen and estrogen receptor expression by antiepileptic drugs and steroids in hippocampus of patients with temporal lobe epilepsy

Abstract: Summary Purpose:  Many of the antiepileptic drugs (AED) used in therapy of temporal lobe epilepsy (TLE) are known as cytochrome P450 (CYP, P450) inducers. These AEDs are thought to modulate androgen and estrogen pathways in hippocampus, and therefore cause mental and reproductive disorders found in TLE patients. In the present study, we analyzed expression of androgen receptor (AR), estrogen receptor α (ERα), and CYP3A in the hippocampus of TLE patients and in murine hippocampal cell line HN25.1. Methods:  Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 54 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…In most tissues, endogenous ER expression is controlled by the abundance of estrogen; ER expression is low in the presence of lower estrogen levels and high when estrogen is high (44,45). For example, treatment of temporal lobe epilepsy patients with P450-inducing anti-epileptic drugs (phenytoin and carbamazepine) increased the level of E2 in patients causing a significant upregulation of ERα mRNA and proteins in their hippocampal pyramidal neurons (46,47). Here, we show that wild-type PCDH19 associates with NONO and, directly or indirectly, affects ERα-mediated gene expression, which is further enhanced in the presence of E2.…”
Section: Discussionmentioning
confidence: 99%
“…In most tissues, endogenous ER expression is controlled by the abundance of estrogen; ER expression is low in the presence of lower estrogen levels and high when estrogen is high (44,45). For example, treatment of temporal lobe epilepsy patients with P450-inducing anti-epileptic drugs (phenytoin and carbamazepine) increased the level of E2 in patients causing a significant upregulation of ERα mRNA and proteins in their hippocampal pyramidal neurons (46,47). Here, we show that wild-type PCDH19 associates with NONO and, directly or indirectly, affects ERα-mediated gene expression, which is further enhanced in the presence of E2.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-epileptic drug s such as oxcarbazepine, carbamazepine and phenytoin are potent inducers of CYP3A4 in human hippocampal pyramidal neurons [32]. CYP3A4 metabolizes testosterone and estradiol [33, 34], both of which are neuroactive steroids that can influence mood, behavior, sexuality, memory and cognition [35].…”
Section: Insight Into the Functional Role Of Cyps In The Brainmentioning
confidence: 99%
“…AEDs could be locally metabolized, resulting in the loss of therapeutic efficacy or production of neurotoxic molecules [20]. AEDs, such as oxcarbazepine, carbamazepine, and phenytoin, are associated with CYP3A4 in human hippocampal pyramidal neurons [68]. As a result, induction of CYP3A4 metabolism in the brain can alter brain function.…”
Section: Routes Of Drug Biotransformationmentioning
confidence: 99%
“…In addition, earlier studies showed CYP3A4 expression (in protein and mRNA) to be significantly elevated in epileptic brain endothelial cells, isolated from brain resections of DRE, when compared with commercially procured, control brain endothelial cells [7,8]. Patients treated with AED have higher expression of both androgen receptors and CYP3A4 in the hippocampus compared with patients with untreated epilepsy [68]. Similarly, administration of phenytoin to mice leads to the induction of androgen receptor expression in the hippocampus [69].…”
Section: Routes Of Drug Biotransformationmentioning
confidence: 99%